OMG! Iz Txt Spk wrecking our language? / Khairunisa Nikman, Norzie Diana Baharum and Rosdin Rosly - Nikman, Khairunisa; Baharum, Norzie Diana; Rosly, Rosdin (2013)
Language, generally, is one form of communication tool that is constantly changing and evolving. New electronic media like e-mail, instant messaging, text messaging, personal web pages and blogs have created multiple forms of communication styles for various purposes and audiences. English language, commonly labeled as the international lingua franca, is also not immune to this change. With this evolution, people are changing the way they communicate with each other. Due to the excessive use of mobile phones and internet, people - unintentionally -are more prone to use the short message service (SMS) lingo in their communication. Students, being teenagers, are the most affected party. Several studies revealed that text speak affects students' writing skill, while some claimed that this new communication style does not give any impact on students' literary performances. Therefore, this paper aims to look into the overview of the use of text speak among teenagers and its influence on students' writing skills.